2018
DOI: 10.1111/aswp.12146
|View full text |Cite
|
Sign up to set email alerts
|

How long is the queuing for public childcare facilities in Korea? An empirical analysis of Korean households' childcare mode choice with the limited availability of public childcare facilities

Abstract: This paper empirically investigates Korean households' choice of childcare mode using the Korean Childcare Users Survey (2012). A multivariate logit model with partial observability (hereafter, PO-logit model) is employed to address the issue of Korean households' demand for public childcare facilities exceeding capacity limits.Our estimation result rejects the hypothesis of no queueing at conventional significance levels to advocate use of the PO-logit model in explaining Korean households' childcare choices.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Among the 3,498 service recipients, 15 percent of parents (512 individuals) had preferences for the public sector, 4% (138) preferred the nonprofit sector, 15% (530) expressed preferences for the for-profit sector, and 66% (2,318 persons) had no particular preferences. The similar percentage of public sector and for-profit sector preferences indicated a stronger predisposition toward the public sector than the nonprofit or for-profit sectors, considering the limited supply capacity of public childcare facilities discussed earlier (Woo & Jun, 2018). The results also showed that 54% of parents with pro-public sector preferences ended up as public recipients, and 66% of those with pro-nonprofit sector preferences ended up as nonprofit recipients.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Among the 3,498 service recipients, 15 percent of parents (512 individuals) had preferences for the public sector, 4% (138) preferred the nonprofit sector, 15% (530) expressed preferences for the for-profit sector, and 66% (2,318 persons) had no particular preferences. The similar percentage of public sector and for-profit sector preferences indicated a stronger predisposition toward the public sector than the nonprofit or for-profit sectors, considering the limited supply capacity of public childcare facilities discussed earlier (Woo & Jun, 2018). The results also showed that 54% of parents with pro-public sector preferences ended up as public recipients, and 66% of those with pro-nonprofit sector preferences ended up as nonprofit recipients.…”
Section: Resultsmentioning
confidence: 61%
“…This phenomenon can be explained by the contract failure theory, which argues that citizens have a favorable attitude toward organizations with nonprofit status because they are legally prohibited from distributing profit (Hansmann, 1980). Similarly, pro-public sector preferences tend to be observed in the context of Korean public childcare services (Ministry of Health and Welfare and Korea Institute of Child Care and Education [MHW and KICCE], 2018;Woo & Jun, 2018).…”
Section: Citizen Sector-based Preferences Of Public Service Organizat...mentioning
confidence: 99%